Tata Rias Wajah Pengantin Arab Indonesia Modern - Hikmah, Nurul; Faidah, Mutimmatul (Journal of Beauty and Cosmetology (JBC), 2019)
Arabian bride's makeup has sharp and glamorous makeup characteristics. This study aims to describe the design and embodiment of makeup for modern Arab brides. The type of research method used is the type of qualitative descriptive method. The data collection methods used are interviews and observation. Data analysis techniques using the formula mean / average. The results showed: (1) The results became the embodiment of modern Arab bridal makeup in accordance with the designs that have been made with very good ratings. (2) The results of the embodiment of modern Arab bridal face makeup received good grades and were accepted by respondents. Keywords: characteristics of Arab brides; Arabian brides; Arabian makeup